Electron-Beam Inactivation of Human Rotavirus (HRV) for the Production of Neutralizing Egg Yolk Antibodies - Skrobarczyk, Jill W.; Martin, Cameron L.; Bhatia, Sohini S.; Pillai, Suresh D.; Berghman, Luc R. (Frontiers in Immunology, 2022)
Electron beam (eBeam) inactivation of pathogens is a commercially proven technology in multiple industries. While commonly used in a variety of decontamination processes, this technology can be considered relatively new to the development of vaccines and therapeutics. Rotavirus is the leading cause of severe gastroenteritis among infants, children, and at-risk adults. Infections are more severe in developing countries where access to health care, clean food, and water is limited. Passive immunization using orally administered egg yolk antibodies (chicken IgY) is proven for prophylaxis and therapy of viral diarrhea, owing to the stability of avian IgY in the harsh gut environment. Since preservation of viral antigenicity is critical for successful antibody production, the aim of this study was to evaluate the use of electron beam inactivation as an alternative pathogen inactivation method for producing rotavirus-specific neutralizing egg yolk antibodies. White leghorn hens were immunized with the eBeam-inactivated viruses every 2 weeks until serum antibody titers peaked. The relative antigenicity of eBeam-inactivated Wa G1P[8] human rotavirus (HRV) was compared to live virus, thermally, and chemically inactivated virus preparations. Using a sandwich ELISA (with antibodies against recombinant VP8 for capture and detection of HRV), the live virus was as expected, most immunoreactive. The eBeam-inactivated HRV’s antigenicity was better preserved when compared to thermally and chemically inactivated viruses. Additionally, both egg yolk antibodies and serum-derived IgY were effective at neutralizing HRV in vitro. Electron beam inactivation can be a suitable alternative for the inactivation of HRV and other enteric viruses for use in both passive and active immunization strategies.